Mesophase pitch production from fluorine-pretreated FCC decant oil. (15th November 2022) - Lim, Chaehun; Hwan Kwak, Cheol; Ko, Yoonyoung; Lee, Young-Seak
Highlights: Effect of fluorine treatment over FCC-DO for mesophase formation firstly suggested. Reaction mechanism of mesophase formation by fluorination was suggested. Fluorine promoted radical polymerization of FCC-DO to form heavy mesophase nuclei. The amount of hydrogen donating species also increased after the fluorination. Pitch from fluorinated DO had higher mesophase yield than pitch from pristine DO. Abstract: Petroleum residue oil-based mesophase pitch production suffers from its low yield of mesophase. There have been continuous efforts, such as catalyst-assisted reactions and multistep heat treatments, to produce high-purity mesophase pitch. However, most of these techniques have difficulties with the processability. In this study, we suggest a novel fluorine pretreatment of fluid catalytic cracking (FCC) decant oil for mesophase pitch (MP) production. The effects of fluorine pretreatment on FCC decant oil were evaluated with mass spectrometry (MS) and their hydrogen donating ability. Subsequently, the MPs from pristine pitches with fluorine pretreatment were intensively compared in terms of structural, thermal, and chemical characteristics. From these results, it was found that fluorine pretreatment helps mesophase formation by catalytic radical polymerization but does not cause coking and does not require posttreatment. It was found that the fluorination method can also provide an effective method for generating MP by increasing the hydrogen donating ability (HDA) fraction. We believe that the results of this work could inspire new insights into MP production.